Flexible 1D Batteries: Recent Progress and Prospects - Zhu, Yun‐Hai; Yang, Xiao‐Yang; Liu, Tong; Zhang, Xin‐Bo (Advanced materials (Weinheim), 2020)
With the rapid development of wearable and portable electronics, flexible and stretchable energy storage devices to power them are rapidly emerging. Among numerous flexible energy storage technologies, flexible batteries are considered as the most favorable candidate due to their high energy density and long cycle life. In particular, flexible 1D batteries with the unique advantages of miniaturization, adaptability, and weavability are expected to be a part of such applications. The development of 1D batteries, including lithium‐ion batteries, zinc‐ion batteries, zinc–air batteries, and lithium–air batteries, is comprehensively summarized, with particular emphasis on electrode preparation, battery design, and battery properties. In addition, the remaining challenges to the commercialization of current 1D batteries and prospective opportunities in the field are discussed. The latest advances in flexible 1D batteries, including metal‐ion batteries and metal–air batteries, are summarized, with particular emphasis on electrode preparation, battery design, and electrochemical and mechanical properties. Additionally, future perspectives on and remaining challenges to the practical application of 1D batteries are also discussed to promote the commercialization of 1D batteries.